Exploiting Flaws in Big Data Systems - Brown, Michael G.; Centonze, Paolina (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this journal we discuss the relevant security threats, vulnerabilities and prominent techniques to securing data lake. Over the last few years, Big Data solutions to data processing have made remarkable strides in the how we interpret data. Because of its ubiquitous nature and ability to handle various data types, it has become a valuable tool and asset to many other fields including bioinformatics solutions, marketing solutions, and social media. Ethical infractions also play a role in data processing and because of this, it is critical that comprehensive security solutions are determined and enforced under the appropriate conditions. Although modern security techniques are well developed, they still leave room for scrutiny as vulnerabilities continue to unfold.Â In this paper, we will examine and compare modern ethical exploit techniques as well ass techniques to promote greater authentication and overall perimeter security. The scrutinization of the current methods met through exploitation, be it physical or conceptive, is imperative in defining the understanding and verification of definite secure solutions. Â